Review of Existing Platforms, Gaps and Challenges in CIS delivery in Zambia - Amarnath, Giriraj; Alahacoon, Niranga; Koppa, Nisha; Sharma, Tarul; Ngowenani, Nohayi; Jacobs-Mata, Inga (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Understanding the information about the organizations that provide the data helps to identify the problems and challenges that arise in the generation and distribution of data in those organizations and help them to better solve and make them more efficient. The impotent issue identified through this survey is the low trend in the use of satellite-based data in information generation. Therefore, to avoid this, and strengthening the geospatial literacy, it is important to develop training programs on the use of Earth observation data. The respondents of this questionnaire survey also expressed the need for such training. On the other hand, it was shown that the use of social media is very low in the dissemination of data and information, so it is timely important to take measures to increase it uses because the majority of people have a high tendency to use social media. As the highest percentage of end-users of CIS are farmers and agricultural sector, successful CIS system can ensure food security through increasing agricultural production. Floods and droughts dominate Zambia's climate-related hazards. Similarly, Diarrhea, Flu epidemics and malaria are major among the diseases and epidemics caused by climatic hazards. One of the most striking findings from the study is the increased focus on forecasting, early warning and mitigation in the providing of flood-related services. Even in the provision of drought-related services, considerable attention has been paid to warning and mitigation. However, it is noteworthy that monitoring and mapping based on satellite data is low in both flood and drought disasters. According to the perception of the respondent, more than 97% of the respondents to the study expressed their willingness to collaborate with the Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) initiative on procuring any of the CIS. Organizations that responded to the questionnaire indicated below how CIS could be improved through the AICCRA program.